Adherence to the Mediterranean diet is associated with lower cancer-related fatigue: a cross-sectional analysis from NHANES 2017–2020 - Xueqin Xia; Xuehua Cao; Chen Gong; Yi Liu; Xiaoyuan Zhang; Limei Liao (Frontiers in Nutrition)
Background and objectivesCancer-related fatigue is a common and distressing symptom experienced by cancer patients, which may persist from the time of diagnosis to the end of life. This fatigue negatively affects patients’ physical, emotional, and cognitive well-being. Nutrition plays a key role in managing cancer-related fatigue, and recently, the Mediterranean diet has gained attention as a potential intervention. The present study uses data from the National Health and Nutrition Examination Survey (NHANES) to investigate the association between cancer-related fatigue and the Mediterranean diet.MethodsData from the NHANES 2017–2020.03 cycle were selected for this cross-sectional study. The Alternative Mediterranean Diet Adherence (AMED) score was used to evaluate the participants’ adherence to the Mediterranean diet. AMED scores were calculated based on data from 24-h dietary recall interviews conducted on both day one and day two. Multiple linear regression modeling was used to explore the association between AMED scores and cancer-related fatigue, as well as the relationship between AMED scores and fatigue in the general population.ResultsA total of 6,413 adults aged 20 years and older were included in the study, with 707 identified as cancer patients. There was a noteworthy inverse relationship found between AMED scores and fatigue, which was more pronounced in cancer patients: β = −0.121, 95% CI: −0.172, −0.071 (p < 0.001) in the unadjusted model. This correlation remained significant after adjusting for all variables in model 3: β = −0.074, 95% CI: −0.127, −0.021 (p = 0.007). A significant dose-dependent relationship was found when AMED scores were expressed in quartiles, with a more pronounced negative association as AMED increased across all models (p for trend <0.05). In the cancer population, the analysis of individual nutrients and fatigue revealed that alcohol was significantly negatively associated with cancer-related fatigue in all models, particularly in the unadjusted model: β = −0.710, 95% CI: −1.058, −0.362 (p < 0.001). Subgroup analyses indicated that diabetes, education level and type of cancer had a significant effect on the relationship between AMED and fatigue, with interaction p-values of 0.010, 0.023 and 0.049, respectively.ConclusionThe present study suggests that higher adherence to the Mediterranean diet may contribute to reduce fatigue, especially in cancer patients; however, further research is necessary to validate this correlation.